Novel Based Approach towards Diabetic’s Classification Using Artificial Intelligence and Internet of Things Environment - Divyashree R; Dr. Sumati Ramakrishna Gowda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The work is focused on designing effective technique employing AI such as machine learning and Internet of things environment for diabetic classification and management. The model is focused in reliably and energy efficient manner in collecting data using IoT and edge-computing paradigm. The work is focused on designing a novel ML model that can classify diabetics and should address class imbalance issues. The model should also be robust considering different kinds of data/attributes related to diabetics.